Eratosaster ... - Mah, Christopher L. (Zenodo, 2011)
Eratosaster nov. gen. Diagnosis. As for species. ... : Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 24, DOI: 10.5281/zenodo.276783 ...